HUBUNGAN PEMANFAATAN BUKU TEKS DAN LINGKUNGAN SEKOLAH DENGAN HASIL BELAJAR IPS - Rahmat Guret; M. Fahri Yasin (Akademika : Jurnal Teknologi Pendidikan, 2019)
This study aims to examine whether or not there is a meaningful relationship between textbooks and the school environment with the results of learning social science both one by one and together. This research was conducted at the junior high school (SMP) which is located in the Bekasi City environment. The time of implementation this research is carried out from November to February 2019. For the independent variables, namely the use of textbooks and the school environment, the data was collected using questioner. The measuring instrument uses a likert scale, while the final variable is the result of learning social science whose instruments use a multiple choice test. The research method used to explain the relationship between the research variables is the survey method. Testing the validity of the textbook and school environment using the product moment formula and the reliability calculation using the Alpha formula of Social Sciences using the biserial point correlation formula and reliability calculation using the KR-20 formula. Data analysis techniques using statistical tests in the form of correlation and simple linear regression and multiple correlations and regression. Hypothesis testing is carried out at a significant level.This research produces three main conclusions, namely:(1) There is a positive and significant relationship between the use of textbooks and learning outcomes of Social Sciences (IPS). (2) There is a positive and significant relationship between the school environment and the learning outcomes of Social Sciences (IPS). (3) There is a positive and significant relationship between the relationship between the use of textbooks and the school environment together with the learning outcomes of Social Sciences (IPS).